2020
DOI: 10.18662/brain/11.2sup1/89
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Big Data and Machine Learning in COVID-19

Abstract: The big rise in the existence of digital data contributed to creating many good chances, especially related to corporations, institutions and firms. Also, it gives the capability to scrimp data regarding its major or area, where the countries have benefited from the analysis of big data (BD) greatly in the face of epidemics and diseases, especially COVID-19 since BD is now available everywhere around us, from official reports and scientific studies related to virology and epidemiology. The general aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Machine learning and big data are capable of making a lot effort in the fight against COVID-19, like as analyzing epidemiological models, creating interactive dashboards, and recommending the optimal vehicles for getting treatments of virus [31]. Ababneh et al in [31] demonstrated that using reinforcement learning to analyze big data provides effective and tremendous results, despite a number of challenges and restrictions.…”
Section: Related Workmentioning
confidence: 99%
“…Machine learning and big data are capable of making a lot effort in the fight against COVID-19, like as analyzing epidemiological models, creating interactive dashboards, and recommending the optimal vehicles for getting treatments of virus [31]. Ababneh et al in [31] demonstrated that using reinforcement learning to analyze big data provides effective and tremendous results, despite a number of challenges and restrictions.…”
Section: Related Workmentioning
confidence: 99%
“…By mixing the human with the machine (the creature with his creator), this can be very helpful to get good results [14], which will enrich the process of learning. Also, machine learning has the ability to learn from any experience [15]. A lot of machine learning samples exist, but the most known or popular ones are of both kinds; supervised and unsupervised.…”
Section: Machine Learning In Educationmentioning
confidence: 99%
“…A lot of machine learning samples exist, but the most known or popular ones are of both kinds; supervised and unsupervised. The first one is specialized in helping the samples by using the dataset, but the second one works by following some results with a self-learning method from the sample itself [15].…”
Section: Machine Learning In Educationmentioning
confidence: 99%
“…Additionally, research results showed that most Pandemic countries were transforming into smart cities using machine learning based on big data analytics [8]. However, Angdhiri, (2020) stated that many educational institutions are not ready to implement home learning programs during the pandemic.…”
Section: Introductionmentioning
confidence: 99%